MEETING BEHAVIORAL HEALTH NEEDS OF OLDER VETERANS: EVALUATING PROGRAMS ACROSS THE CONTINUUM OF CARE. (11th November 2018) - Karel, M J; Conwell, Y
Abstract: Integrated, interdisciplinary care models have shown promise for addressing behavioral health care needs of older adults. Behavioral health services have been integrated into Veterans Health Administration (VHA) primary and geriatric care settings, to optimize access to care for veterans with mental illness, behavioral and psychological symptoms of dementia, and/or suicide risk, and their caregivers. It is critical to develop and evaluate innovative programs to meet the complex needs of veterans in these care settings. This symposium reviews strategies for and outcomes of evaluation of impact of four such programs. In New York and New Jersey, a telehealth program that aims to improve dementia identification and caregiver support in primary care shows promising systemic, caregiver, and cost outcomes. A national program to train Home Based Primary Care (HBPC) clinicians in a 6-session Problem Solving Training (PST) intervention shows promising clinical outcomes, and positive clinician and veteran feedback. The national STAR-VA program to train Community Living Center (CLC) teams to understand and manage behavioral symptoms of dementia expanded its evaluation to examine the program's impact across types of target behaviors of concern (e.g., physically or verbally aggressive/non-aggressive). A critically important pilot program, Suicide Awareness for Veterans Exiting the CLC, is addressing the increased risk of suicide among veterans recently discharged from CLC settings by evaluating the feasibility and preliminary outcomes of post-discharge phone calls focused on depression and suicide risk. A non-VA geriatric mental health leader will help to discuss the implications of this work.